Aplikasi M-Learning Berbasis Html5menggunakan Jquery Mobile - Imam Soleh Ma’rifati - AMIK BSI Purwokerto (Evolusi : Jurnal Sains dan Manajemen, 2015)
Abstract Number of internet users increase rapidly nowadaysand according to the Ministry of Communications and Information Technology of Indonesia, 80% of internet users are between 15-19 years old, this means most of them are students at high school. In educational field, internet also  used to presents learning material to students. This known as electronic learning (e-learning). E-learning using the internet to present learning materials to students who access using a computer or laptop. Along with the advance of new communication technologies like smartphone, tablet and other mobile device, e-learning also use the new technology to access learning materials. E-learning that use mobile deivice known as mobile-learning (m-learning). The concept of mobile-learning is e-learning, which focuses on the use of mobile devices to access learning media. M-learning applications needed to access and present the materials or media that is accessible via mobile devices. Because the mobile data card has different characteristics to a desktop computer or laptop, then the m-learning applications also had to adapt the device beeing used.Developing application for mobile device can be achieved throught web tecnology as a web base application. Web base application can build using HTML 5, a new version of HTML, a language to present information. Using HTML 5, we can build web base application more easier bacause this aplication can be accessed using diferent device with single code. This is very advantageous because the application does not need to be made in different versions for each device used to access the application. In this study,we developed an application for m-learning based on a  HTML 5 framework  called Jquery Mobile. Model for developing application use the waterfall model, while stages in development process refers to system development life cycle (SDLC). The result is a web base application for m-learning. It is intended to use mobile device to access the learning materials.   Keywords:  M-Learning, web base aplication, HTML5, Jquery Mobile.